Tinjauan sistematis tentang preservasi warisan musik - Gani Nur Pramudyo; Tamara Adriani Salim (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. The awareness of musical heritage shows an effort of preservation that performed by composers, musicians, performers, archivists, conservators, local society, community archivists, and government. Data Collection Methods. The paper used a systematic review method with a qualitative approach represented by literature from Taylor & Francis database. Data Analysis. A multi-stage exclusion process showed nine articles for further review. An analytical grid/chart was used to systematize the most relevant information of the selected articles. A tree illustration (including roots, trunk, and leaves) was used to represent the main idea of each article. Results and Discussion. The raised awareness of the importance of preservation can be supported by creating the music projects, promoting music for tourism, and music repackaging. We categorize seveal aspects of preserving heritage music such as 1) understanding the integrity of the original trace and media, 2) combining prescriptive & descriptive documentation 3) musical repackaging method, and 4) using Art Glove device. Conclusion. A synthesis of proposals was developed to illustrate the musical heritage preservation that represents ideas of selected articles that have been reviewed. In addition, this study also allows the researchers to identify gaps in the literature and research directions.